Sarcopenic obesity is associated with coffee intake in elderly Koreans - Lee, Do-Youn; Shin, Sunghoon (Frontiers in Public Health, 2023)
This study assessed the association between sarcopenic obesity (S+O+) and coffee intake inelderly Koreans. This study obtained data from the Korea National Health and Nutrition Examination Survey (KNHANES, 2008–2011), a cross-sectional and nationally representative survey conducted by the Korean Centers for Disease Control and Prevention. Of the 2,661 participants included in this study, there was a significant difference between 5.861 (95% CI 2.024–16.971) in less than one cup of coffee, and 6.245 (95% CI 2.136–18.260) in one cup of coffee, and 4.323 (95% CI 1.457–12.824) in two cups of coffee compared to three or more than cups of coffee. In contrast, in the case of sarcopenia or obesity only (S+O- or S-O+), no significant difference was found in any model. The results suggest that the elderly who consume less than one cup of coffee per day had a greater risk of S+O+ than those who consume more than three cups per day. Furthermore, there was an association between coffee intake and sarcopenia but not with obesity. Therefore, coffee intake may have prevented musculoskeletal loss in these patients.